Literature Study on Implementation of Elementary School Student Character Education : Studi Literatur Implementasi Pendidikan Karakter Siswa Sekolah Dasar - Lestari, Putri Retno; Tirtoni, Feri (Indonesian Journal of Education Methods Development, 2021)
This study aims to find out the implementation process in leadership character education in elementary school students which is reviewed from the performance of school management and the implementation process. The method used in this study is the study of literature using descriptive research methods. The result is that the performance of school management towards the implementation of character education of elementary school students through 3 stages, namely planning, implementation and evaluation. While in the process of implementation of education karater leadership of elementary school students in the form of programs strengthening spiritual attitudes and behaviors, leadership character forming learning programs, student habituation through leadership learning, habituation of students carrying out responsibilities, and habituation of students through decision making. The implementation of primary school student leadership character education can be applied in accordance with the stages of each implementation process.